2007
DOI: 10.1016/j.ejphar.2007.03.031
|View full text |Cite
|
Sign up to set email alerts
|

NIH 11082 produces anti-depressant-like activity in the mouse tail-suspension test through a delta-opioid receptor mechanism of action

Abstract: The present study examined the effects of NIH 11082 ((−)-(1R,5R,9R)-5,9-dimethyl-2'-hydroxy-2-(6-hydroxyhexyl)-6,7-benzomorphan hydrochloride), a benzomorphan analogue, in the mouse tail suspension, an assay used to detect antidepressant agents. NIH 11082 significantly decreased immobility time during tail suspension, with a comparable magnitude as the tricyclic antidepressant desipramine. Importantly, NIH 11082 failed to elicit convulsions or other overt behavioral signs of toxicity. The delta-opioid receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 15 publications
4
22
0
1
Order By: Relevance
“…This report sought to expand on those findings and shows that RGS4 plays a complex role in regulating DOPr-mediated antidepressant-like effects, depending on the type of assay employed. In wild-type mice, SNC80 produced decreases in immobility in the forced swim and tail suspension tests, consistent with previous work showing that DOPr agonists produce antidepressant-like effects in these assays (Broom et al 2002a; Naidu et al 2007; Saitoh et al 2011). In both assays, SNC80 produced U-shaped dose effect curves, such that larger doses of SNC80 (10 mg/kg in TST, 32 mg/kg in FST) failed to produce significant antidepressant-like effects.…”
Section: Discussionsupporting
confidence: 91%
“…This report sought to expand on those findings and shows that RGS4 plays a complex role in regulating DOPr-mediated antidepressant-like effects, depending on the type of assay employed. In wild-type mice, SNC80 produced decreases in immobility in the forced swim and tail suspension tests, consistent with previous work showing that DOPr agonists produce antidepressant-like effects in these assays (Broom et al 2002a; Naidu et al 2007; Saitoh et al 2011). In both assays, SNC80 produced U-shaped dose effect curves, such that larger doses of SNC80 (10 mg/kg in TST, 32 mg/kg in FST) failed to produce significant antidepressant-like effects.…”
Section: Discussionsupporting
confidence: 91%
“…Several selective DOP receptor agonists reduced depressive-like behaviors in animal tests, including SNC80, NIH11082, UFP512, KNT-127, and AZD2327 [for a review, see (Chung and Kieffer, 2013)]. The antidepressant-like effects were comparable to those produced by selective serotonin reuptake inhibitors and tricyclic antidepressants (Naidu et al, 2007; Saitoh et al, 2004). DOP receptor agonists decreased anxiety- and depression-like behaviors in mice withdrawn from alcohol and cocaine (Ambrose-Lanci et al, 2010; Perrine et al, 2008; van Rijn et al, 2010)…”
Section: Introductionmentioning
confidence: 99%
“…97 The list includes more than a dozen agonists, from a variety of chemical structural classes. 69,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] Interestingly, at least one study suggests that the antidepressant activity of the tricyclic antidepressant imipramine might be mediated by DOR. 116 Concomitantly, it has been suggested that the effects of tricyclic antidepressants on neuropathic pain require DOR stimulation, at least in mice.…”
Section: Other Therapeutic Potentialmentioning
confidence: 99%